(untitled) (Research, Society and Development, 2021)
The occurrence of incisional hernias in pigs is poorly described, so the objective of the study is to report a case of incisional hernia in pig treated with polypropylene mesh. A 1 year old male, mixed breed pig weighing 22 kg was treated at the HVU-UFOB. During the anamnesis, the owner reported that the animal had swelling in the abdominal region, having a suggestive diagnosis of umbilical hernia, confirmed by ultrasound. In view of the findings, it was decided to perform herniorrhaphy with direct suture. Ten days after surgery, adequate healing of the surgical wound was verified with the absence of a hernial ring. Fifty-one after surgery, the animal returned with an increase in abdominal volume at the surgery site. On physical examination, the presence of a 12 cm ring and reducible intestinal loops in the hernial sac were identified. After a new ultrasound examination, the diagnosis of incisional hernia was defined. A new herniorrhaphy with polypropylene mesh was chosen. After 10 days, the wound healing was verified. Incisional hernias in pigs are generally related to the animal’s age, sex, breed and species, as well as flaws in the surgical technique. Biological or synthetic materials are used for the correction, in order to reinforce safety in the incision line. One year after herniorrhaphy, there was no recurrence, which shows a satisfactory result with the use of the polypropylene mesh.